Implementasi Project Based Learning dalam Meningkatkan Pemahaman Siswa pada Konsep Ekonomi Berkelanjutan - Nendi, Ikhsan; Lestari, Anisa Ayu Dwi; Saona, Saona; Alifah, Nur; Hidayat , Agus Rohmat (Universitas Hamzanwadi, 2025)
This study aims to examine the effectiveness of project-based learning in improving students' understanding of the concept of sustainable economy. The study used a quantitative approach with a cross-sectional design, involving 200 high school students in Cirebon Regency who were selected through random sampling techniques. The research instrument was a Likert scale questionnaire, with validity and reliability tested using Pearson Product Moment and Cronbach Alpha coefficients. The results showed that project-based learning significantly improved students' understanding of the concept of sustainable economy. The t-test analysis revealed significant differences based on gender, where female students had a higher level of understanding than male students. The ANOVA results showed significant differences in students from public and private high schools (F = 5.678, p < 0.05), while Pearson's correlation indicated a positive relationship between age and student understanding (r = 0.453, p < 0.01). This study provides practical and theoretical contributions in integrating project-based learning into the curriculum, while supporting constructivist theory in education. Limitations of the study include limited geographic coverage and cross-sectional design. Further research is recommended to use a longitudinal design and expand the scope of the area.